Economic Incentives and the Quality of Return Migrant Scholars: The Impact of China's Thousand Young Talents Program - Ning Jia; Belton M. Fleisher (Institute of Labor Economics (IZA), 2020)
We study the effect of the Thousand Young Talents Program (TYTP) on the academic quality of return migrant scientists to China. Using a unique dataset of the top Chinese mathematics departments' new hires, we find that the program leads to considerable increases in measures of their educational background and research productivity. The effects are concentrated in the elite C9 league, where the proportion of hires who received PhD degrees from top-50 overseas mathematics departments increased nearly four times after the initiation of the program. The data also reveal large and statistically significant increases in weighted pre-hire publications and weighted citations to pre-hire publications under the program. However, it appears that research output of previously hired faculty members declined after the introduction of TYTP hires, suggesting minimal or even negative impact of TYTP on faculty colleagues' academic achievements.
Keywords: J61; O31; O38; 330; migration; scientific research; R&D policy